1995
DOI: 10.1002/ajh.2830480205
|View full text |Cite
|
Sign up to set email alerts
|

Morphologic and ultrastructural evidence for interleukin‐6 induced platelet activation

Abstract: The in vitro effect of IL-6 on platelet activation was investigated. When human platelets were incubated with high (1,000 ng/ml) or low (1 ng/ml) dose IL-6, expression of GMP-140 was enhanced by 42% (N = 6; P < 0.009) and 46% (N = 6; P < 0.061) in 1 hr low and high dose IL-6-platelet incubations, respectively, as assessed by flow cytometry. In platelet specimens incubated with high dose IL-6 for 3 hr, a 70% (N = 6; P < 0.009) increase in GMP-140 expression over control was observed. Parallel high dose IL-6 inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
17
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 18 publications
2
17
0
Order By: Relevance
“…Addition of ng/mL concentrations of IL-6 (approximately X1000 the concentration used here) resulted in increased expression of p-Selectin and significant alternations in platelet morphology and intracellular ATP levels. 8 . Although no activational effects from IL-8 have been reported, previous data have shown that platelets express functional IL-8 receptors on their membranes that are upregulated in inflammatory disease states, and that potentially could respond to levels of the exogenous ligand.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Addition of ng/mL concentrations of IL-6 (approximately X1000 the concentration used here) resulted in increased expression of p-Selectin and significant alternations in platelet morphology and intracellular ATP levels. 8 . Although no activational effects from IL-8 have been reported, previous data have shown that platelets express functional IL-8 receptors on their membranes that are upregulated in inflammatory disease states, and that potentially could respond to levels of the exogenous ligand.…”
Section: Discussionmentioning
confidence: 99%
“…Fresh platelets were incubated with exogenous cytokines at levels that routinely accumulate in platelet products, and activation was assayed by measuring the expression ofp-Selectin (CD 62) on the surface of the platelets. [4][5][6][7][8] Our studies provide evidence that platelets are directly activated by IL-6 and IL-8 at concentrations that accumulate during routine storage of platelet products, thus potentially contributing to the platelet storage lesion.…”
mentioning
confidence: 99%
“…It was recently shown that some cytokines, such as granulocyte-colony stimulating factor (G-CSF; 11), stem cell factor (SCF; 12), IL-6 (13), and thrombopoietin (TPO; 14 -17), modulate platelet activation. In particlular, Oda et al (15) reported that TPO dose dependently increased initial velocity as well as the maximum extent of SIPA.…”
mentioning
confidence: 99%
“…Cytokines also affect platelet activation or aggregation. For example, granulocyte-colony stimulating factor (G-CSF) [21], stem cell factor (SCF) [22], IL-6 [23] and thrombopoietin (TPO) [24][25][26][27] modulate platelet activation. In particular, Oda et al [25] reported that TPO dose-dependently increased the initial velocity as well as the maximum extent of SIPA.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, there are many reports that some cytokines modulate platelet function. For example, in vitro studies by Oleksowicz et al [23,42] utilizing human platelets have shown that IL-6 enhances agonist-induced platelet aggregation, enhances granules and thromboxane B 2 secretion, and stimulates platelet cytoskeletal assembly, and have also indicated based on electron-microscopic findings that IL-6 has a platelet-activating effect as well as enhanced P-selectin expression. In addition, G-CSF is reported to enhance ADP-induced platelet aggregation [21], and SCF enhances secondary aggregation by ADP or epinephrine [22].…”
mentioning
confidence: 99%